Dental and oral health students' preparedness for the management of deaf patients: A cross-sectional survey - Anooshree Katwe; Scott Santarossa; Sherrie Beaver; Agnieszka Frydrych; Omar Kujan (Elsevier, 2023)
Background/purpose: The communication barrier that deaf people face when seeking dental care can impact their experience and may potentially lead to exacerbated dental fear or anxiety. This study aimed to investigate the current attitudes and levels of knowledge and confidence of Australian oral and dental health students in treating a deaf patient. Materials and methods: A 33-item cross-sectional questionnaire was distributed to Australian dental, oral health therapy and dental hygiene students across 13 tertiary institutions. The online questionnaire was distributed to students via their respective course coordinators. Results: 271 viable survey responses were received. While 55.7% of participants reported previous exposure to deaf or hard-of-hearing people, 90.8% had never completed or attempted an Auslan class. These participants who answered 'Yes' to having taken a prior Auslan class were reported to have significantly higher mean knowledge scores and confidence self-efficacy ratings than those who had answered 'No' (p = 0.002). There was no statistically significant association between higher knowledge scores and higher confidence self-efficacy ratings. Most of these participants that answered 'Yes' to having taken a prior Auslan class implied or stated that the party responsible for changing their communication behaviour was the dentist rather than the patient, in contrast to the inconsistent responses from the 'No' group. Conclusion: Inadequate knowledge and cultural competency regarding the Deaf population was reported by Australian dental, oral health therapy and hygiene students. Incorporating more training pertinent to dental curricula is warranted to minimise oral health inequalities.